(untitled) (Bangladesh Journal of Medicine, 2021)
The COVID-19 pandemic, caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV- 2) is causing a worldwide pandemic of COVID-19 within a short span of time. Although patients with COVID-19 primarily present with fever and respiratory illness; a wide range of symptoms involving different systems have been described. While the neurological sequelae of the virus remain poorly understood, there are a growing number of reports of neurological manifestation of COVID-19.The neurological manifestation including both central and peripheral nervous system are increasingly reported in a very subset of COVID-19 patients. The SARS-CoV-2 enters the body mainly via the ACE- 2 receptors within the respiratory system, which causes the body to initiate an immunologic response against potential damage to non-renewable cells. There’s increasing evidence of accumulating that COVID-19, particularly in severe cases, can have neurological consequences although respiratory symptoms nearly always develop before neurological ones. Patients with pre-existing neurological conditions could also be at elevated risk for COVID-19 associated neurological symptoms. The neurological presentations of COVID-19 patients maybe acute and post-acute state. The acute presentations are classified into specific (such as stroke, encephalitis, acute polyneuropathy, etc.) and nonspecific (such as delirium, headache, dizziness, etc.) symptoms with anatomical involvement of either central nervous system including brain or spinal cord, and/or peripheral nervous system, neuromuscular junctions or muscles. Several neurological symptoms have also been demonstrated in post-acute or long covid-19 syndrome. There is a possibility to overlook or misinterpretation of, neurological symptoms in some COVID-19 patients. In infants and young children, the foremost common CNS phenomena are febrile seizures; in adults, non-focal abnormalities will be either neurological or constitutional. To date, neurological manifestations of COVID-19 are described largely within the disease trajectory, and also the long-term effects of such manifestations still remain unexplored and unfolded. This article is intended to review the possible neuro-invasive routes of SARS-CoV-2 and its mechanisms which initiate the neurological damage with neurological presentations of COVID-19 patients. Bangladesh J Medicine July 2021; 32(2) : 120-137